Orthographic Reading Deficits in Dyslexic Japanese Children: Examining the Transposed-Letter Effect in the Color-Word Stroop Paradigm - Ogawa, Shino; Shibasaki, Masahiro; Isomura, Tomoko; Masataka, Nobuo (Frontiers in Psychology, 2016)
In orthographic reading, the transposed-letter effect (TLE) is the perception of a transposed-letter position word such as “cholocate” as the correct word “chocolate.” Although previous studies on dyslexic children using alphabetic languages have reported such orthographic reading deficits, the extent of orthographic reading impairment in dyslexic Japanese children has remained unknown. This study examined the TLE in dyslexic Japanese children using the color-word Stroop paradigm comprising congruent and incongruent Japanese hiragana words with correct and transposed-letter positions. We found that typically developed children exhibited Stroop effects in Japanese hiragana words with both correct and transposed-letter positions, thus indicating the presence of TLE. In contrast, dyslexic children indicated Stroop effects in correct letter positions in Japanese words but not in transposed, which indicated an absence of the TLE. These results suggest that dyslexic Japanese children, similar to dyslexic children using alphabetic languages, may also have a problem with orthographic reading.